Layanan Bimbingan Klasikal Dampak Phubbing pada Siswa Kelas VII SMP Negeri 25 Banjarmasin - Ali Rachman; Muhammad Andri Setiawan; Jessica Ester Bawimbang; Faisal Rachman (Universitas Mathla'ul Anwar Banten, 2019)
CLASSICAL GUIDANCE SERVICES IMPACT PHUBBING IN CLASS VII STUDENTS OF SMP NEGERI 25 BANJARMASIN. Millennial generation is inseparable from the use of smart phones as the latest communication technology media. The negative impact that is felt from the development of smart phones is the birth of phubbing behavior which means the act of ignoring others when interacting with social communication with more focus on paying attention to cellphones. Departing from these problems, it is necessary to provide classical guidance services on the effects of phubbing. What was done in SMPN 25 Banjarmasin was based on the request of partners, namely the SMPN 25 Banjarmasin guidance teacher based on the results of developing practical conditional information in the field. Implementation of classical guidance services. To find out the description of phubbing behavior in class VII students, the Generic Scale of Phubbing (GSP) instrument is used before and after service delivery. The results of the implementation of the service showed that this classical guidance service was successful in reducing students becoming phubbing actors. It is suggested that the implementation of classical guidance services can be a preliminary study for phubbing research.